Sulistina Peran Pojok Baca, Sumber Literasi, Keterampilan Menyimak : Peran Pojok Baca, Sumber Literasi, Keterampilan Menyimak - Sulistina Sulistina; Moh. Rudini; Hamna Hamna; Sulistina Sulistina; Moh. Rudini; Hamna Hamna (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2026)
The reading corner is a supporting program for the School Literacy Movement (GLS). SDN 1 Tinigi is one of the schools that has provided a reading corner, but its use is still limited to the habituation stage. This is the background for this research to be conducted with the aim of describing (1) The role of the reading corner as a source of literacy in improving the listening skills of 5th grade students of SDN 1 Tinigi, (2) Supporting and inhibiting factors in implementing the reading corner for 5th grade students of SDN 1 Tinigi. Using a mixed method approach with data collection through observation, interviews and documentation shows that the reading corner plays a role as a source of literacy in improving listening skills as seen from the large number of 5th grade students of SDN 1 Tinigi getting good grades. Acting as a source of literacy, the reading corner has 4 roles, namely as a facility for students to read in class, as a provider of nearby reading materials for students, as a comfortable place for students to read and as an interesting place for students to read. The supporting factor for implementing the reading corner in 5th grade students of SDN 1 Tinigi is that it is updated regularly. Meanwhile, the inhibiting factor in implementing the reading corner in class 5 of SDN 1 Tinigi is the students' low interest in reading.